Following the Heart: Ethics of Doing Affective Ethnography in Vulnerable Research Settings - Ferdiansyah Thajib (International Quarterly for Asian Studies, 2022)
This paper chronicles my fieldwork among Muslim queer people in Indonesia. The ethical thrust of “following the heart” lies in the continuous reinvention of research devices in order to keep up with what we feel during, before and after fieldwork, how we are affected by encounters with others, and how others are affected by us. This idea of “following what the heart tells one to do” can be traced back to the old opposition between body and mind, where the head is thought to be rational and cold, and the heart is considered to be emotional and warm. Here, I truncate the metaphor’s dichotomous meaning and discuss the potential values of applying it as an ethics of doing affective ethnography in vulnerable settings. Anthropological knowledge production in vulnerable contexts is not only about providing careful interpretation and representation of the affective experiences of our research participants, but also about making ourselves affectively vulnerable as researchers. This ethics is both a method and a source, remaining existentially inscribed into the researchers’ embodied realities and continuing to shape our academic practices and everyday livings.